Community structure and distribution pattern of gastropods in the mangrove ecosystem in Bolihutuo Village, Boalemo, Gorontalo - Daulima, Novia; Kasim, Faizal; Kadim, Miftahul Khair; Paramata, Arfiani Rizki (Universitas Malikussaleh, 2021)
This study aimed to investigate the community structure and distribution pattern of Gastropods in the mangrove ecosystem Bolihutuo village. The study was conducted in February and July 2021 in two different stations. Community structure analysis carried out includes species composition, density, diversity, evenness, dominance, and distribution patterns by Morisita dispersion index. The results showed that 13 species of gastropods were found from 8 families, namely Cassidula nucleus, Littoraria palescens, Chicoreus capucinus, Nasarius distortus and Phrontis polygonata, Nerita planospira, Faunus ater, Pirenella alata, Cerithidea obtuse, Telescopium Telescopium, Terebralia palustris, Terebralia sulcata and Monodonta labio. Gastropod diversity of each station in June was relatively higher than observations in February. The distribution of Gastropods has a clustered, random, and uniform pattern.Keywords: Community structure; distribution pattern; Gastropods; Mangrove; Bolihutuo